Gender‐Typed Behaviors in Friendships and Well‐Being: A Cross‐Cultural Study of Chinese and American Boys. (14th February 2013) - Gupta, Taveeshi; Way, Niobe; McGill, Rebecca K.; Hughes, Diane; Santos, Carlos; Jia, Yueming; Yoshikawa, Hirokazu; Chen, Xinyin; Deng, Huihua
<x xml:space="preserve">Abstract</x> This 3‐year, longitudinal analysis examined the psychological and social correlates of adhering to gender‐typed behaviors in friendships among boys during middle school in United States (N = 446, Mage = 11.37 years) and in China (N = 368, Mage = 12.20 years). Results indicated that boys did not differ by nationality in the mean levels or in the increase over time in adherence to gender‐typed behaviors. Furthermore, adherence over time was associated with higher depressive symptoms, lower self‐esteem, and lower friendship quality for boys in both countries. However, the associations between gender‐typed behaviors and friendship quality and depressive symptoms were stronger for boys in the United States. Our study suggests that gender‐typed behaviors play an important role in the well‐being of youth in different parts of the world.